Healthcare workers' perceptions of an organizational quality assurance program implemented in a resource-limited setting: A qualitative study - Henker, H; Fox-Lewis, S; Tep, N; Vanna, D; Pol, S; Turner, C (Tabriz University of Medical Sciences, 2018)
Background There is increasing awareness of the need to implement quality assurance programs in developing countries. Healthcare staff are the primary drivers of improving the quality of care, but little is known about how they perceive quality assurance programs in resource-limited settings. This study aims to evaluate healthcare workers’ perceptions of the organizational quality assurance program (OQA) at Angkor Hospital for Children (AHC), Cambodia. The OQA involves regular data collection and monitoring of quality indicators, to assess whether agreed quality standards are being met. Methods This qualitative study consisted of four focus group discussions (FGDs) with 29 hospital staff (convenience sampling) from medical, nursing and non-medical departments. Staff members’ understanding of quality assurance and perceptions of the strengths and weaknesses of the OQA were explored. Thematic content analysis was used to identify key themes. Results Participants emphasized that quality indicators must include physical and psychological well-being. Strengths of the OQA included shared understanding amongst all groups of participants of its goals, committed leadership, that it was locally-relevant and that target indicators were developed from a “ground-up” approach. On-going challenges included that there was a gap in understanding of the OQA processes and overall running of the OQA across the organization between managers and staff. Conclusion The introduction of the OQA at AHC has been well-received by staff members. Overall, the program is perceived to be valuable. Healthcare provision in resource-limited settings increasingly needs to demonstrate quality assurance. The model of OQA developed at AHC is one way to achieve this.